ANALISIS PERBANDINGAN KINERJA KEUANGAN KOTA SURABAYA SEBELUM DAN SAAT PANDEMI COVID-19 - Mardiana, Yunita; Dwiyani, Alfiani; Lating, Ade Irma Suryani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study aims to analyze the financial performance of the Surabaya City Government before and during the COVID-19 pandemic. The research method used is quantitative descriptive by collecting secondary data from the Surabaya City Government Budget Realization Report from 2019 to 2021. The data is analyzed using several financial ratios, such as economic ratios, efficiency and effectiveness ratios, degree of fiscal decentralization, spending harmony ratios, and financial dependence. The results showed that the financial performance of the Surabaya City Government experienced a significant decline during the COVID-19 pandemic, especially in 2020. However, the Surabaya City Government still managed to maintain its financial performance well and obtained an unqualified opinion from the Supreme Audit Agency.